Magnetic state in URu₂Si₂, UPd₂Al₃, and UNi₂Al₃ probed by point contacts - Naidyuk, Yu. G.; Kvitnitskaya, O. E.; Jansen, A. G. M.; Wyder, P.; Geibel, C.; Menovsky, A. A. (Физика низких температур, 2001)
The antiferromagnetic (AFM) state has been investigated in the three heavy-fermion compounds URu₂Si₂,UPd₂Al₃, and UNi₂Al₃ by measuring dV/dI(V) curves of point contacts at different temperatures 1.5-20 K and magnetic fields 0-28 T. The zero-bias maximum in dV/dI(V) for URu₂Si₂ points to a partially gapped Fermi surface related to the itinerant nature of the AFM state, contrary to the case of UPd₂Al₃, where analogous features have not been found. The AFM state in UNi₂Al₃ has more similarities with URu₂Si₂. For URu₂Si₂, the same critical field of about 40 T along the easy axis c is found for all features in dV/dI(V), corresponding to the Néel temperature, the gap in the electronic density of states, and presumably the ordered moments. The antiferromagnetic (AFM) state is investigated in the three heavy-fermion compounds URu₂Si₂, UPd₂Al₃, and UNi₂Al₃ by measuring dV/dI(V) curves of point contacts at different temperatures 1.5–20 K and magnetic fields 0–28 T. The zero-bias maximum in dV/dI(V) for URu₂Si₂ points to a partially gapped Fermi surface related to the itinerant nature of the AFM state, contrary to the case of UPd₂Al₃, where analogous features have not been found. The AFM state in UNi₂Al₃ has more similarities with URu₂Si₂. For URu₂Si₂, the same critical field of about 40 T along the easy axis c is found for all features in dV/dI(V), corresponding to the Néel temperature, the gap in the electronic density of states, and presumably the ordered